(untitled) (Ukrainian Journal of Ophthalmology, 2023)
This is a review on compressive optic neuropathy (CON) in the setting of tumors of the chiasmal and sellar region. CON is a difficult to manage neuro-ophthalmological condition that occurs when the optic nerve is damaged due to compression of the anterior visual pathway, commonly by scull-base tumors of the middle and anterior fossae. Compression of the optic nerve/chiasm complex is accompanied by reduced vision, visual field defects and descending optic atrophy, which, if not treated properly, can lead to permanent vision loss and blindness. The literature data on the prevalence and features of visual disturbances in chiasmal-sellar tumors which differ in histology have been reviewed.